Theoretical Study on Falling Film Absorption Inside Swaying Tube With TFE/NMP Solution - 刘艳丽; 徐士鸣 (Zhileng xuebao)
According to the characteristics of the falling film absorption in the absorbers employed on boats, a physical and mathematical model of momentum, heat and mass transfer of falling film absorption in a swaying tube with TFE/NMP solution was established. The model takes into account the effects of swaying accessional inertia forces on the distributions of film thickness, velocity, temperature, and concentration of falling film. A combination of integral and completely implicit finite volume method was adopted to solve the governing equations. By analyzing the computational results, it is shown that the distributions of the parameters inside the falling film, such as velocity, temperature, and concentration, take on the traits of periodicity and symmetry due to the existence of the swaying accessional inertia forces in the process of the falling film absorption under a swaying status using TFE/NMP as working fluid.